2007
DOI: 10.1111/j.1460-9592.2007.02331.x
|View full text |Cite
|
Sign up to set email alerts
|

Children who refuse anesthesia or sedation: a survey of anesthesiologists

Abstract: Cancellation of planned surgery because of child refusal is not uncommon. It is important to recognize the potentially uncooperative child, particularly older children with developmental delay or a lack of understanding. Discussion with child and parents, selective use of premedication and different induction agents, distraction, play techniques, gentle restraint and the option of cancellation and review should all be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 24 publications
3
38
0
Order By: Relevance
“…Our results reflect those of Lewis et al 24 in that our participants were more uncomfortable restraining more mature minors. It is likely that this reflects increasing respect for the minor's emerging autonomy and the need to proceed with, what Ross terms, proportionate respect 25.…”
Section: Discussionsupporting
confidence: 90%
“…Our results reflect those of Lewis et al 24 in that our participants were more uncomfortable restraining more mature minors. It is likely that this reflects increasing respect for the minor's emerging autonomy and the need to proceed with, what Ross terms, proportionate respect 25.…”
Section: Discussionsupporting
confidence: 90%
“…Findings from Lewis et al. () study indicated that only 44% ( n = 194) of anaesthetists held the majority of children (<1 year old) for anaesthetic induction; this perhaps reflects the fact that anaesthetists have access to alternative strategies such as gas inhalation that leads to children being held for a very short time or for holding to be avoided. Naber et al.…”
Section: Resultsmentioning
confidence: 99%
“…The concept of safety referred to in these studies focuses purely on physical safety and little consideration appears to have been given to consider the child's psychological or ethical well‐being and safety Several studies link safety to the perceived urgency or necessity for a procedure to be completed (Robinson and Collier ; Graham and Hardy ; Lewis et al. ; Homer and Bass ), with professionals more likely to use holding when a procedure was seen as clinically important and urgent (Lewis et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…Further study of training differences is important because it may illuminate missed educational opportunities regarding the evolving role of the maturing minor in health care decision-making. Although our scenarios were oncology based, there is a growing literature regarding treatment refusals in pediatrics [26][27][28][29]37], as well as issues of noncompliance or nonadherence which may be an alternative nonconfrontational way of expressing a refusal [38][39][40]. …”
Section: Discussionmentioning
confidence: 98%
“…In addition, it primarily focuses on understanding decisions in cases that progress to court intervention [19][20][21][22][23]. Although this is an area of growing interest and research [26][27][28][29], discussions afford little to no consideration to the attitudes of pediatricians with respect to refusals. Because pediatricians see and react to far more refusals than those which come before courts, understanding their attitudes is an important step in understanding treatment refusals for minors generally.…”
mentioning
confidence: 99%